Granulocyte Macrophage-Colony Stimulating Factor (GM-CSF) Downregulates the Expression of Protumor Factors Cyclooxygenase-2 and Inducible Nitric Oxide Synthase in a GM-CSF Receptor-Independent Manner in Cervical Cancer Cells. (15th July 2015) - Jiang, Nanyan; Tian, Zhiqiang; Tang, Jun; Ou, Rongying; Xu, Yunsheng
Abstract : Enhanced expression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) is associated with the pathogenic processes of various tumor types. COX-2 and iNOS expression in the immunomodulatory dendritic cells is mediated by the granulocyte macrophage-colony stimulating factor (GM-CSF), which is also expressed by cervical cancer cells; however, whether and how GM-CSF regulates COX-2 and iNOS expression in clinical cervical cancer cells remain unknown. In this study, we found that the COX-2 and iNOS expression was upregulated in the cervical cancer tissues and positively correlated with cancer metastasis and stage. About one-half of the cervical cancer tissues showed strong/moderate GM-CSF expression, while the normal cervical tissues showed >80% positive rate; no GM-CSFR protein was detectable on the cervical cancer cells. The GM-CSF expression was negatively correlated with the COX-2 and iNOS expression in the cervical cancer tissues and the functional negative regulatory effect of GM-CSF on COX-2/iNOS expression was demonstrated in various cervical cancer cell lines. Therefore, in cervical cancer cells, GM-CSF might contribute an antitumor response by inhibiting iNOS and COX-2 expression in a GM-CSFR independent manner.